1 + 2 ! 2 3 + 3 ! 3 3 + 4 ! 4 3 + ⋯ = k × e
What is k ?
Notation: e ≈ 2 . 7 1 8 2 8 denotes the Euler's number .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Calvin Lin , @Pi Han Goh - check the solution
Log in to reply
Wonderfully written. This is the way that I would have solved it....
nicely done i did the way sir @Chew-Seong Cheong did
super solution
I simply guessed 4 without analysis but calculated to be 5.
S = 1 + 2 ! 2 3 + 3 ! 3 3 + 4 ! 4 3 + ⋯ = n = 1 ∑ ∞ n ! n 3 = n = 0 ∑ ∞ ( n + 1 ) ! ( n + 1 ) 3 = n = 0 ∑ ∞ n ! ( n + 1 ) 2 = n = 0 ∑ ∞ n ! n 2 + 2 n + 1 = n = 0 0 ! 1 + n = 1 1 ! 4 + n = 2 ∑ ∞ n ! n ( n − 1 ) + 3 n + 1 = 5 + n = 2 ∑ ∞ ( ( n − 2 ) ! 1 + ( n − 1 ) ! 3 + n ! 1 ) = 5 + n = 0 ∑ ∞ n ! 1 + 3 n = 1 ∑ ∞ n ! 1 + n = 2 ∑ ∞ n ! 1 = 5 + n = 0 ∑ ∞ n ! 1 + 3 ( n = 0 ∑ ∞ n ! 1 − 0 ! 1 ) + n = 0 ∑ ∞ n ! 1 − 0 ! 1 − 1 ! 1 = 5 n = 0 ∑ ∞ n ! 1 = 5 e
Alternate approach could be :
e x = 1 + 1 ! x + 2 ! x 2 + 3 ! x 3 + ⋯
Differentiate both sides wrt to x,and then multiply by x,
x e x = x + 2 ! 2 x 2 + 3 ! 3 x 3 + ⋯
Observe that if we differentiate both sides again wrt to x, we will get 2 2 , 3 2 , 4 2 , . . . . as coefficients on numerator . Thus if we again repeat the above procedure,ie, by again multiplying by x and differentiating,we will get cubes in the numerator,and then by putting x =1,we will get the required result.
I Did the same way!
n = 1 ∑ ∞ n ! n 3 = n = 1 ∑ ∞ ( n − 1 ) ! n 2 − 1 + 1 = n = 1 ∑ ∞ ( ( n − 2 ) ! n + 1 + ( n − 1 ) ! 1 )
= n = 1 ∑ ∞ ( ( n − 3 ) ! 1 + ( n − 2 ) ! 3 + ( n − 1 ) ! 1 ) = 5 e
Hence k = 5 .
Problem Loading...
Note Loading...
Set Loading...
e x = 1 + 1 ! x + 2 ! x 2 + 3 ! x 3 + 4 ! x 4 + ⋯ ⋯ Differentiating w.r.t x on both sides e x = 1 ! 1 + 2 ! 2 x + 3 ! 3 x 2 + 4 ! 4 x 3 + ⋯ ⋯ Multiplying both sides by x x e x = 1 ! x + 2 ! 2 x 2 + 3 ! 3 x 3 + 4 ! 4 x 4 + ⋯ ⋯ Again differentiating w.r.t x on both sides e x ( x + 1 ) = 1 ! 1 + 2 ! 2 2 x + 3 ! 3 2 x 2 + 4 ! 4 2 x 3 + ⋯ ⋯ Again Multiplying both sides by x x ( x + 1 ) e x = 1 ! x + 2 ! 2 2 x 2 + 3 ! 3 2 x 3 + 4 ! 4 2 x 4 + ⋯ ⋯ Again differentiating w.r.t x on both sides ( x 2 + 3 x + 1 ) e x = 1 ! 1 + 2 ! 2 3 x + 3 ! 3 3 x 2 + 4 ! 4 3 x 3 + ⋯ ⋯ Put x=1 , we get 5 e = 1 + 2 ! 2 3 + 3 ! 3 3 + 4 ! 4 3 + ⋯